2021
DOI: 10.3390/foods10081853
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Accumulation of Human Enteric Viruses and Phages in Process Water from the Fresh Produce Industry

Abstract: The virological quality of process water (PW) used by the produce industry has received limited attention. As a first step to overcoming technical limitations in monitoring viruses in PW, the analytical performance of ultrafiltration was assessed to concentrate viral particles from 20 L of spiked PW. The selected method used for sample concentration of PW was carefully validated, thus enabling the accurate quantification and estimation of viral titers of human enteric viruses and phages. PW from the produce in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
1
4
0
Order By: Relevance
“…positive (Cuevas-Ferrando et al, 2021). In support of this, our study demonstrated the average prevalence rates of crAssphages in irrigation water and fresh leafy greens were 61 and 68.5%, respectively.…”
Section: Discussionsupporting
confidence: 84%
“…positive (Cuevas-Ferrando et al, 2021). In support of this, our study demonstrated the average prevalence rates of crAssphages in irrigation water and fresh leafy greens were 61 and 68.5%, respectively.…”
Section: Discussionsupporting
confidence: 84%
“…One aim of this study was to characterize the antiviral efficacy of chlorine and non-chlorinating agents (e.g., chlorine dioxide and PAA) in PW from three processing operations over time. There is only limited information on the effects of organic matter present in PW on the disinfection performance of human enteric viruses and phages (Cuevas-Ferrando et al, 2021). Some PW characteristics, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…Physicochemical parameters, together with classical microbial indicators, such as fecal indicator bacteria, including fecal coliforms, Escherichia coli, and enterococci have been widely used to assess the quality of PW used in different postharvest operations. However, studies investigating the presence of human enteric viruses or viral indicators are limited (Cuevas-Ferrando et al, 2021;Dunkin et al, 2017;López-Gálvez et al, 2016;Moreno et al, 2015;Ortiz-Solà et al, 2020). Sanitizers are considered processing aids regulated by the EU (Regulation (EC) No 1333/2008).…”
Section: Introductionmentioning
confidence: 99%
“…Electrical Conductivity (EC, μS/cm) is the capacity of water to transmit an electrical current and is affected by dissolved solids, which correlated with organic load and should be determined for each type of process water and product (Gombas et al., 2017; Cuevas‐Ferrando et al., 2021; López‐Gálvez et al., 2021).…”
Section: Assessmentmentioning
confidence: 99%
“…Mostly due to the increase of COD in process water where PAA is being used, the measurement of turbidity has been recommended for the assessment of the physico-chemical quality of PAA-treated process water (L opez-G alvez et al, 2020). Electrical Conductivity (EC, lS/cm) is the capacity of water to transmit an electrical current and is affected by dissolved solids, which correlated with organic load and should be determined for each type of process water and product (Gombas et al, 2017;Cuevas-Ferrando et al, 2021;L opez-G alvez et al, 2021).…”
Section: Most Common Disinfection Treatments Used To Maintain the Mic...mentioning
confidence: 99%